2003
DOI: 10.1046/j.1464-5491.2003.00871.x
|View full text |Cite
|
Sign up to set email alerts
|

Is birth weight related to later glucose and insulin metabolism?—a systematic review

Abstract: The published literature shows that, generally, people who were light at birth have an adverse profile of later glucose and insulin metabolism. This is related to higher insulin resistance, but the relationship to insulin secretion in adults is less clear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
274
5
12

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 407 publications
(316 citation statements)
references
References 74 publications
25
274
5
12
Order By: Relevance
“…Our finding of a possible U-shaped association between birthweight and type 2 diabetes is in agreement with some studies [19,20], but most report an inverse relationship (reviewed in [3]). In agreement with Whincup et al (1997) [21], we found that the post-natal growth effect was stronger than the pre-natal effect indicated by birthweight.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our finding of a possible U-shaped association between birthweight and type 2 diabetes is in agreement with some studies [19,20], but most report an inverse relationship (reviewed in [3]). In agreement with Whincup et al (1997) [21], we found that the post-natal growth effect was stronger than the pre-natal effect indicated by birthweight.…”
Section: Discussionsupporting
confidence: 93%
“…Food rationing will also have reduced differences related to socio-economic status in maternal and childhood diets, compared with those differences in subjects born at other times [17]. Our finding that the relationship of early life growth with type 2 diabetes was largely accounted for by current adult BMI is in agreement with one study [18], but not with those of a later one [3]. It is, of course, possible that the processes that determine adiposity rebound occur in the antenatal period, but we have no data to investigate that.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Gupta et al found higher insulin resistance among Indian low BW children [28] whereas in the UK no association was observed in children [10,11]. Evidence that BW affects HOMA%b is inconclusive [12]. There are reports that low BW was associated with elevated HOMA%b [5], whereas others did not found an association [1,2,26].…”
Section: Interpretation Of the Findingsmentioning
confidence: 99%
“…However, some studies have reported that current adult BMI is associated with insulin resistance regardless of BW and postnatal growth [10,11]. Studies have also assessed the effect of these factors on insulin secretion but results are not consistent [1,5,12,13].…”
Section: Introductionmentioning
confidence: 99%